Performance investigation on plate heat exchanger using nanofluid as working fluid / Ler Cherk Yong - Lee, Cherk Yong (2011)
Plate heat exchanger (PHE) is a kind of heat transfer equipment that made up of a pack of thin corrugated metal plate that promote heat transfer between two fluids. Water as the most common heat transfer medium has low thermal conductivity that result in lower overall heat transfer coefficient. With rising interest in fluid with higher thermal conductivity offered by dispersing nanoparticles in base fluid, called ―nanofluids‖, researchers are investigating the advantages of applying this fluid in conventional heat transfer devices. In this study the performance of an existing PHE in oil and gas industry is investigated when the alumina (Al2O3) and silicon dioxide (SiO2) nanofluids of various particle size and volume fraction was introduce as the hot fluid medium. In addition, the advantages of utilizing nanofluids as the heat transfer medium in the PHE design are examined. In this study, it‘s found that the application of Al2O3 with 3% particle volume concentration nanofluids in the existing PHE system resulted the heat transfer rate increased by 1.29% and correspondingly 2.66% of the volumetric flow rate can be reduce to achieve the similar rated heat transfer rate. For SiO2 nanofluids, it‘s distinguished that the highest heat transfer rate could be achieved by 1.5% particle volume concentration. In PHE design, the heat transfer area to achieve the rated PHE heat transfer rate of 460kW was reduce by 3.08% to 3.21% depending on the desired NTU when using Al2O3 nanofluids of 3% volume fraction. Meanwhile, it‘s observed that the reduction of heat transfer area is dependent on the nanoparticles size as the nanofluids with 25nm SiO2 particles require less heat transfer area compare to the nanofluids with 100nm SiO2 particles.